Professionalism Qualification of Teachers and the Teaching of Social Studies in Junior Secondary Schools: Implication for Quality Instructional Delivery - Bethel C, Uzoagba (International Journal of Educational and Psychological Sciences, 2024)
Teaching arguably is a process of imparting knowledge to the leaner or actions aimed at guiding pupils through series of planned activities to enable them acquire intended skills, knowledge and ability or a way of transferring information to a group of learners. This paper x-rays the implications of the infiltration of general practitioners or nonprofessionals on the pedagogical advancement of Social Studies education as well as the methods through which the subject-learner friendly nature of the subject can be best achieved such as; Field-trips, community resources, demonstrations, resource persons, films, slide and film strip projections, etc. The following findings were made: inadequate knowledge of Social Studies content poor attitudinal disposition among the teachers and inadequate knowledge of Social Studies methods affect the classroom instructions. On the basis of the findings, it was recommended among others that employment of Social Studies teachers should be purely based on professional competencies and relevance, there should be regular training and retraining of Social Studies teachers and Social Studies teachers should be encouraged to developed positive attitude towards the teaching of the subject.